Analisis Sistem Persediaan Bahan Baku Air Kelapa pada Industri Nata de Coco (Studi Kasus PT Keong Nusantara Abadi) - Pangesti, Shella Puji; Saty, Fadila Marga; Riniarti, Dewi (Jurnal Agro Industri Perkebunan, 2019)
Inventory is an important thing for the industrial company, so determination of order quantity must be done optimally and reduce the inventory cost.  PT Keong Nusantara Abadi is an industrial company for processing of nata de coco that requires an inventory control system so that the purchase of raw material becomes optimal.  Therefore, this research was conducted to analyze inventory control carried out by PT Keong Nusantara Abadi and determine alternative methods of inventory control of raw material for the company.  This research use Material Requirement Planning (MRP) system.  MRP system has two ways to determine the order quantity called lot sizing decision.  Techniques for determining the quantity of order is Economic Order Quantity (EOQ), Lot for Lot (LFL), and Part Periode Balancing (PPB).  The technique of determining the order quantity that is best use by PT Keong Nusantara Abadi is EOQ which result in lower inventory cost than inventory control techniques by the company that is saved by 9%, 10%, 7,3% consecutively during 2015, 2016, and 2017.